Semi-Micro Determination of Some Antidepressants in Pure Form and in Their Pharmaceutical Preparations with Ammonium Metavanadate(V) Reagent - Pandey, A.K. (Asian Journal of Chemistry, 2010)
The semi-microdetermination of some antidepressant pure compounds and their pharamaceutical preparations with ammonium metavanadate(V) reagent has been done.